2012
DOI: 10.4194/1303-2712-v12_3_13
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study, the phylogenetic and phylogeographic relationships among Cyprinion macrostomus HECKEL, 1843, Cyprinion kais HECKEL, 1843 and Carasobarbus chantrei SAUVAGE, 1882 samples from Anatolia was analysed. While doing this, mitochondrial DNA polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and Nuclear DNA inter-simple sequence repeat (ISSR) were used. PCR amplified the complete mtDNA NADH ¾ dehydrogenase (ND-3/4) gene. Amplified fragment was digested by 14 restriction enzymes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In this sense, the dietary inclusion of bee pollen altered liver cells increasing their reserves, although in our study, higher reserves did not reflect on higher growth performance and HSI/VSI indexes probably due to short-term bee pollen feeding regime. On the other hand, a complementary effect may occurs as described by Abbass et al (2012) in a study of juvenile Nile tilapia (~45 g) fed with pollen and propolis. The authors reported that inclusion of such additives had protective effects against hepatic damage and renal lesions.…”
Section: Liver Analysismentioning
confidence: 82%
See 3 more Smart Citations
“…In this sense, the dietary inclusion of bee pollen altered liver cells increasing their reserves, although in our study, higher reserves did not reflect on higher growth performance and HSI/VSI indexes probably due to short-term bee pollen feeding regime. On the other hand, a complementary effect may occurs as described by Abbass et al (2012) in a study of juvenile Nile tilapia (~45 g) fed with pollen and propolis. The authors reported that inclusion of such additives had protective effects against hepatic damage and renal lesions.…”
Section: Liver Analysismentioning
confidence: 82%
“…In this study, no improvement was observed in growth performance. As compared to Abbass et al (2012) and El-Asely et al…”
Section: Zootechnical Analysis and Somatic Indexesmentioning
confidence: 90%
See 2 more Smart Citations
“…This species also plays a therapeutic role in medical treatment (Undar et al, 1990). Several workers carried out research on various aspects of the species viz., morphological characteristics (Unlu, 1999), karyotype analysis (Gaffaroglu and Yuksel, 2004), age determination (Aydın et al, 2009), haematology (Duman and Sahan 2014), length-weight relationships (Sedaghat and Hoseini, 2012;Bibak et al, 2013), phylogeographical and phylogenetic relationships between C. macrostomus, C. kais and Carasobarbus chantrei in Euphrates and Tigris rivers (Durna et al, 2012), selected morphometric characteristics (Kara and Gunes, 2015) and morphological differences (Bilici et al, 2015).…”
mentioning
confidence: 99%